1997
DOI: 10.1080/10407789708913879
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Structures of Buoyancy-Induced Flow in a Vertical Channel

Abstract: The present investigation deals with the developflU!nl of low-order represeniations of transitional free convection in a vertical channel with discrete heaters. The governing equations are sowed using a spectral element method. Proper orlhogollll1 decomposuion (POD) is applied to extract the most energetic eigenfunctions (and lhe related spatWlemporaJ structures) from time-dependen: numerical solutions of the full model equations at a Groshof number higher than the critical value. Using the computed eigenfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A more complete description of natural convective heat transfer between vertical parallel plates should analyze the transient behaviors of the full elliptic equations on an extended computational domain. In the following, a short review of the literature on transient laminar natural convection in vertical channels [17][18][19][34][35][36][37][38][39][40] is given.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more complete description of natural convective heat transfer between vertical parallel plates should analyze the transient behaviors of the full elliptic equations on an extended computational domain. In the following, a short review of the literature on transient laminar natural convection in vertical channels [17][18][19][34][35][36][37][38][39][40] is given.…”
Section: Introductionmentioning
confidence: 99%
“…A transient analysis on structures of buoyancy-induced flow in a vertical channel with discrete heaters was accomplished in ref. [39]. A two-dimensional natural convection flow due to periodically spaced heat sources of uniform heat flux and flush mounted on a channel wall was considered.…”
Section: Introductionmentioning
confidence: 99%
“…An open cavity with permeable walls, with all the boundaries open to the surroundings, which considered only half of the entire domain, was assumed as a computational domain. It was observed that [21]. A numerical investigation of the transient regime of natural convection in air, in a vertical channel symmetrically heated at uniform heat flux, was carried out in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of a symmetrically heated vertical channel, at either uniform temperature or uniform heat flux, is reported in [18][19][20][21][22]. A numerical study with the boundary-layer approximation was carried out in [18].…”
Section: Introductionmentioning
confidence: 99%